Entre el oficio de alumno y el habitusde profesor: Los de safíos de la práctica supervisada en el proceso de iniciación a la docencia - de Souza Neto, Samuel [UNESP]; Sarti, Flavia Medeiros [UNESP]; Benites, Larissa Cerignoni [UNESP] (My University, 2016)
This essay focuses on challenges faced by students (interns), university professors (supervisors) and schoolteachers (collaborators) in the process of supervised internship. They face the difficult task of understanding teaching practice regarding the construction of teachers’ identity in Physical Education and Pedagogy. This analysis takes place under the perspective of initiation to teaching understood as interns’ possibility to enter the career and the teaching culture, as well as a possibility for active teachers who contribute to internships to position themselves within the space of teacher education.
Entre o ofício de aluno e o habitus de professor: Os desafios do estágio supervisionado no processo de iniciação à docência
“Between students’ craft and teachers’ habitus: Supervised internship’s challenges in the teaching initiation process
Keywords: Internships; Teachers; Teaching